Software testing : an ISTQB-BCS certified tester foundation guide - Hambling, Brian, 1946- (BCS, The Chartered Institute for IT, 2015)
"This best-selling software testing title explains the basic steps of software testing and how to perform effective tests. It provides an overview of different techniques, both dynamic and static. It is the only official textbook of the ISTQB-BCS Certified Tester Foundation Level, with self-assessment exercises, guidance notes on the syllabus topics with sample examination questions. This third edition includes examples and exercises reflecting current technology and applications, such as the use of open source software, component-based and agile development and application building for mobile devices. It is ideal for those with a little experience of software testing who wish to cement their knowledge with industry-recognised techniques and theory."-- Unedited summary from book.
Includes index.
Keywords: International Software Testing Qualifications Board -- Study guides.; International Software Testing Qualifications Board; Computer software -- Testing -- Examinations -- Study guides.; elektronické knihy; electronic books